All You Need is Love: The Role of Relationships in Transformative Learning as seen in Contemporary Fiction - Randee Lipson Lawrence (Adult Education Research Conference, 2015)
Fiction is the major source of research data in this study of transformative learning. Personal relationships are highlighted as being pivotal to the transformative learning process. Relationships both facilitate and inhibit transformation.
Keywords: fiction; transformative learning; relationships